2016
DOI: 10.1039/c5cp07379k
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of lipid bilayer self-assembly using all-atom lipid force fields

Abstract: In this manuscript we expand significantly on our earlier communication by investigating the bilayer self-assembly of eight different types of phospholipids in unbiased molecular dynamics (MD) simulations using three widely used all-atom lipid force fields. Irrespective of the underlying force field, the lipids are shown to spontaneously form stable lamellar bilayer structures within 1 microsecond, the majority of which display properties in satisfactory agreement with the experimental data. The lipids self-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 68 publications
11
39
0
Order By: Relevance
“…Several combinations of the simulation parameters were tested in order to establish the optimum settings. It was found, as previously described 34 , that an initial simulation using an isotropic pressure scheme, followed by an adequately long semi-isotropic coupling, yielded the best results. In order to favor the membrane formation during the isotropic coupling stage, it was found that the initial cubic simulation box side length has to be commensurate with the side length of the membrane patch, which is expected to be finally formed.…”
Section: Exploratory Self Aggregation Simulations Of the Shc8 Systemsupporting
confidence: 61%
“…Several combinations of the simulation parameters were tested in order to establish the optimum settings. It was found, as previously described 34 , that an initial simulation using an isotropic pressure scheme, followed by an adequately long semi-isotropic coupling, yielded the best results. In order to favor the membrane formation during the isotropic coupling stage, it was found that the initial cubic simulation box side length has to be commensurate with the side length of the membrane patch, which is expected to be finally formed.…”
Section: Exploratory Self Aggregation Simulations Of the Shc8 Systemsupporting
confidence: 61%
“…To be useful, force fields must strike the correct balance between the various intermolecular interactions: biomolecule-water, biomolecule-biomolecule, water-water, water-ion, ion-counterion and ion-biomolecule interactions; in this last case, the main contribution would come from the interaction between the ions in solution and the charged sites of the biomolecules. Classical, fixed-charge force fields for biomolecules in water have been under evolution for decades and are now quite successful at predicting binding affinities 6 and the folded structure of small proteins, 7-9 the self-assembly of phospholipid bilayers, 10 the importance of electrostatics in DNA, and DNA-protein interactions. 11,12 These force fields were parameterized against experimental observables that reflect the balance between ionwater, biomolecule-water and water-water interactions (e.g., free energies of hydration).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Skjevik et al demonstrated that a self-assembled phospholipid structure forms a spontaneous stable lamellar bilayer in few microseconds in an aqueous environment with a clear preferential orientation with polar head groups pointing outside [ 15 ]. However—experimentally—the bilayer packing is related to full water hydration (Van der Waals interactions) through hydrogen bridges [ 14 , 16 , 17 , 18 , 19 ] and lipid interactions [ 20 ].…”
Section: Introductionmentioning
confidence: 99%